FAKTOR YANG MEMPENGGARUHI KINERJA KARYAWAN PADA PT. NASMOCO KALIGAWE SEMARANG - Roistatik, Roistatik; Prabowo, Heri; Sutrisno, Sutrisno (EKOBIS, 2025)
This research was conducted with the aim of analyzing how much influence training and career development has on employee performance with job satisfaction as a mediating variable. This type of research is descriptive quantitative with a population of 114 employees, a sample of 89 respondents using simple random sampling techniques. The data analysis technique uses the partial Least Square (PLS) model with SmarthPLS version 3 software. The results of this research show that: 1) training has a positive and significant effect on job satisfaction at PT Nasmoco Kaligawe. 2) career development has a positive and significant effect on job satisfaction at PT Nasmoco Kaligawe. 3) training has a positive and significant effect on employee performance at PT Nasmoco Kaligawe Semarang. 4) career development has a positive and significant effect on employee performance at PT Nasmoco Kaligawe Semarang. 5) job satisfaction has a positive and significant effect on employee performance at PT Nasmoco Kaligawe Semarang. 6) job satisfaction mediates the effect of training on employee performance at PT Nasmoco Kaligawe Semarang. 7) job satisfaction mediates the influence of career development on employee performance at PT.Nasmoco Kaligawe Semarang.